PROFESSIONAL ADAPTATION AS A FORMATION FACTOR OF FUTURE FLIGHT ATTENDANTS’ READINESS - Радзівілова, І. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The process of professional adaptation of specialists in aviation industry as a factor of formation of future flight attendants’ readiness is considered in the article. Pedagogical literature dealing with the problem of professional adaptation and its influence on formation of specialists’ readiness in different spheres is analyzed. Different approaches to comprehend the concept «adaptation» in Ukrainian and foreign scientific literature are discussed